EMOTIONAL INTELLIGENCE AND JOB SATISFACTION AMONG MEDICAL TEACHING FACULTY - Uzma Bano (Army Medical College Rawalpindi, 2021)
Objective: To measure the correlation between emotional intelligence (EI) and job satisfaction (JS) among teaching faculty of Foundation University Medical College.